2021
DOI: 10.1002/ajb2.1620
|View full text |Cite
|
Sign up to set email alerts
|

Underground carbohydrate stores and storage organs in fire‐maintained longleaf pine savannas in Florida, USA

Abstract: Many perennial herbaceous plants develop underground storage organs (USOs) that store carbohydrates, water, and minerals. The resprouting ability of plants is influenced by the availability of these materials and by the type of underground organ and number of viable buds. In this study, we illustrate the diversity of longleaf pine savanna species and their nonstructural carbohydrate (NSC) pools and concentrations. We also determined whether NSC concentrations by USO are good predictors of NSC pools in species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…There is robust evidence from both experimental studies and field observations that savanna plant species experiencing frequent fires have a larger root mass fraction than those growing free from fires both at the individual species level and ecosystem level (Figure 1C, Table 1) (Boonman et al, 2020;Teixeira et al, 2022;Zhou et al, 2022). Likewise, savanna plant species persisting through frequent fires generally store large amounts of non-structural carbohydrates in specialized root organs (e.g., lignotubers) (Wigley et al, 2009;Clarke et al, 2016;Diaz-Toribio and Putz, 2021), which are critical to support root bud banks and the ability of root sucker for postfire resprouting (Charles-Dominique et al, 2015;da Silva et al, 2020). Similar conservative strategies have also been reported for woody plant resprouters in fire-prone Mediterranean ecosystems (Paula and Pausas, 2011).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…There is robust evidence from both experimental studies and field observations that savanna plant species experiencing frequent fires have a larger root mass fraction than those growing free from fires both at the individual species level and ecosystem level (Figure 1C, Table 1) (Boonman et al, 2020;Teixeira et al, 2022;Zhou et al, 2022). Likewise, savanna plant species persisting through frequent fires generally store large amounts of non-structural carbohydrates in specialized root organs (e.g., lignotubers) (Wigley et al, 2009;Clarke et al, 2016;Diaz-Toribio and Putz, 2021), which are critical to support root bud banks and the ability of root sucker for postfire resprouting (Charles-Dominique et al, 2015;da Silva et al, 2020). Similar conservative strategies have also been reported for woody plant resprouters in fire-prone Mediterranean ecosystems (Paula and Pausas, 2011).…”
mentioning
confidence: 87%
“…Likewise, savanna plant species persisting through frequent fires generally store large amounts of non-structural carbohydrates in specialized root organs ( e.g. , lignotubers) ( Wigley et al., 2009 ; Clarke et al., 2016 ; Diaz-Toribio and Putz, 2021 ), which are critical to support root bud banks and the ability of root sucker for post-fire resprouting ( Charles-Dominique et al., 2015 ; da Silva et al., 2020 ). Similar conservative strategies have also been reported for woody plant resprouters in fire-prone Mediterranean ecosystems ( Paula and Pausas, 2011 ).…”
Section: Root Traits Response To Fires In Savannas: Knowns and Unknownsmentioning
confidence: 99%
“…It was found that, exogenous sucrose can induce longer and more robust rhizomes in perennial rice ( Oryza longistaminata ) [ 13 ]. Higher levels of non-fibrous carbohydrates in rhizome benefited the post-disturbance regeneration of plants [ 14 ]. In the mutants of wheat ( tin ) and rice ( moc 2 ), reduction in sucrose content led to inhibition of tiller growth [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is largely because researchers are often not aware of specialized storage organs (Tribble et al, 2021), use different incompatible methods for carbon storage assessment (Chow & Landhäusser, 2004) and mainly focus on short-term intraspecific variation in carbon storage (Asaeda et al, 2008;Lee & Dunton, 1996;McLaurin et al, 1999). Comparative studies examining interspecific variation in storage across environmental gradients are rare (Janeček et al, 2011;Palacio et al, 2007) and studies evaluating not only storage compound concentration, but also the total storage pool, are nearly non-existent (Diaz-Toribio & Putz, 2021;Klimešová, Janeček, et al, 2017). This has led to highly contrasting opinions about the role of carbon storage in plant life.…”
Section: Introductionmentioning
confidence: 99%
“…Because they are located belowground, they can avoid most major disturbances, and often provide the plant with other functions in addition to carbohydrate storage. These organs are also the centre of perennation because they are usually equipped with dormant buds and serve for vegetative regeneration or clonal growth, thus they can vary in size and shape from conspicuously bulky to long and thin (Diaz-Toribio & Putz, 2021;Tribble et al, 2021). We have only scattered information about biomass investments into storage organs and they are purposefully missing in major analyses of biomass partitioning (Poorter et al, 2015).…”
Section: Introductionmentioning
confidence: 99%